Assistance in the Gate Construction of RT 05 RW 06, Candirenggo Village, Singosari District, Malang Regency: Pendampingan Pembangunan Gapura RT 05 RW 06 Kelurahan Candirenggo Kecamatan Singosari Kabupaten Malang - Gatut Rubiono; Nurida Finahari; Agus Mursidi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
A gate is a physical structure that serves as a marker for a region's identity. Its construction requires appropriate planning and funding. This community service activity aims to provide assistance in the construction of a gate in RT 05 RW 06, Candirenggo Village, Singosari District, Malang Regency. Assistance was provided for the design, drawings plan and budget plan in a proposal, as well as the gate construction process. Construction was funded by community funds and donations from the surrounding community. The assistance process is considered to provide positive benefits, particularly in the preparation of proposals that facilitate fundraising and the construction process.